METODE COOPERATIVE LEARNING MODEL KELOMPOK INVESTIGASI SEBAGAI ALTERNATIF GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS DASAR - Shafir Ubaidillah (BASA Journal of Language & Literature, 2022)
Student learning interest is always a major problem in the learning process. So, teachers need to be as creative as possible in managing class management and creating a conducive and harmonious class, one of which is by applying a learning method with better innovation. Therefore, researchers are eager to conduct a research related to learning methods with the intention and purpose of being able to explain the application of learning methods that can provide an innovation to learning methods, such as the cooperative learning model of the investigative group model. In the research process that will be carried out, the method that will be used is descriptive qualitative research method, with the techniques used, namely interview techniques, observation and documentation at the stage of the data collection process. And using the technique of extension of participation, persistence of observation and triangulation at the stage of the data validity checking process. So that the results obtained show that: being able to further increase students' interest in learning is one of the impacts that will be obtained or the advantages of applying the Cooperative Learning method of investigative group model. In the process of applying this method, a teacher can classify students into several groups and then carry out an investigation related to the learning topic, which will produce a final report that will be presented by representatives of each group to the front of the class. However, there are several obstacles to the learning process of this model, namely the lack of objectivity during the assessment and the lack of harmony between each group, therefore to overcome these problems, the teacher should be more innovative and creative, namely by continuing to provide an active role for students in giving their opinions during the discussion process to support the value of each individual, and to prevent the lack of harmony between groups, the teacher should divide the groups in the class heterogeneously and free each group leader to distribute investigation tasks to each member of his group.